(untitled) (Academia Science Repository, 2023)
This article presents a linguoculturological study of the derivational potential of English word-forming elements of Latin and Greek origin. The study examines the linguistic and cultural aspects of these languages and how they have influenced English. The study identifies the most common word-making elements in English, such as prefixes, suffixes, roots, and combining forms. The study also analyzes the ways in which these elements are used to create new words in English. The article concludes with a discussion of the importance of understanding the Latin and Greek derivational potential of English word-making elements for enhancing language skills and cultural awareness.